HANDLING STRATEGY COMPLAINTS OF APAPO AND WALK-IN PASSPORT SYSTEM APPLICATIONS IN IMMIGRATION OFFICE OF NON-BORDER CONTROL SOUTH JAKARTA - Virza Shalia Agviani (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
The development of information technology has entered into various aspects of public services in various fields. This also occurs in the scope of immigration with the concept of New Public Service (NPS). The NPS can be implemented with several innovations in the form of new products, services and technologies. In the current era of globalization, the public views that service development is a need that should exist. This research was conducted to confirm how or strategies to resolve applicant complaints regarding the passport queuing registration policy, and its benefits in being able to find out the constraints and shortcomings that are owned so that it can optimize the use of the queuing system and can and can also conclude how the implementation should be implemented in order to minimize passport applicant complaint.